Probabilistic Fracture Energy Assessment of Natural Fibre Reinforced Concrete by Two Parameter Weibull Distribution - P Asrani, Neha; G, Murali; J, Arthika; K, Karthikeyan.; M.K, Haridharan. (International Journal of Engineering and Technology, 2018)
Fracture energy is the post-crack energy absorption ability of the material that represents the energy absorbed by the structure at the time of failure. Its analysis has gained importance and hence requires a powerfulmethod for its development. A two parameter Weibull distribution proves to be an efficient tool in analysing the scattered experimental test results. In this paper, the specific fracture energy of plain concrete and concrete reinforced with natural fibres of hemp, wheat straw and elephant grass are statistically analysed by two parameter Weibull distribution by using graphical method. For determining Weibull parameters, 21 equations have been used and the best equation is taken for the reliability analysis. A Weibull reliability curve is plotted, which shows the specific fracture energy at each reliability level. This curve enables an engineer to choose the fracture energy of a particular mix based on its reliability requirement and safety limit. Therefore, reliability curves are a pioneer in statistical analysis as they eliminate the time-consuming and costly experimental process. This method can be applied in areas with similar uncertainties.Â Â